PENGARUH PENAMBAHAN BUBUR WORTEL (Daucus carrota) DAN TEPUNG TAPIOKA TERHADAP SIFAT FISIKOKIMIA DAN SENSORIS BAKSO IKAN GABUS (Ophiocephalus striatus) - Olivia P.M. Purukan; Christine F. Mamuaja; Lucia C. Mandey; Lexie P. Mamahit (COCOS, 2013)
ABSTRACTCork fish balls (Ophiocephalus striatus) is one of the products processed from fish meat shaped cork sphere obtained from fish meat mixed formulations of existing cork and starch in tapioca flour and adding pureed carrots. This study aims to get the fish balls in physicochemical and sensory panelists preferred the addition of pureed carrots treated as a source of natural dyes in fish balls cork. Organoleptic test results, treatment was continued with an analysis of selected physical properties and chemical analysis. Organoleptic test results for fish balls cork that is treated E (10g carrot porridge: 5g tapioca flour) is the most preferred treatment by the panelists. The results for the test fish balls cork texture for fish balls cork on the chosen treatment is the treatment formula E = (10g carrot porridge: tapioca flour 5g) was 1.69 mm / gr / sec. With the analysis of the chemical properties of the water content of 77.36%, ash content 1.54%, 13.38% protein, 1.19% fat, 0.57% crude fiber, total carbohydrate 5.96%, and the content of vitamin A <0.5 IU.Keywords : Cork fish ball, pureed carrots, tapioca flour